Geoglyphs and formative-period activity in the middle Chillón Valley, Peru: Ceramic association and null-model tests of route proximity - Christian Mesía-Montenegro; Ángel Sánchez-Borjas (PLoS ONE, 2026)
Geoglyphs are widespread in arid landscapes, but their chronology and relationship to movement corridors are often difficult to evaluate where direct dating is unavailable. This study examines four geoglyph groups documented through systematic pedestrian survey and RPAS-based recording in two quebradas of the middle Chillón Valley, central coast of Peru: Huarabí (n = 2) and Pichausa (n = 2). Chronological inference is necessarily limited. Diagnostic Formative-period ceramics were recorded only in Huarabí, where they indicate nearby activity rather than directly dating geoglyph construction. Pichausa remains chronologically unresolved. To evaluate whether the documented geoglyphs occur closer to mapped route proxies than expected under explicit counterfactual assumptions, we measured nearest-route distances from within-geoglyph sampling points (k = 20 per geoglyph; n = 80 total) and from six unweighted Formative ceramic findspots in Huarabí. Observed distance distributions were compared with Monte Carlo simulations in which geoglyph shapes were randomly repositioned within defined survey windows while route geometries remained fixed. Across 999 simulations, Huarabí deviates from the tested null model under the survey-polygon window, or buffer = 0 m (p = 0.021), whereas Pichausa does not (p = 0.380). Results vary substantially under broader availability windows, indicating that inference is strongly conditioned by how potential placement space is defined.. These findings provide exploratory, model-dependent evidence that some Huarabí geoglyph contexts and associated ceramic findspots occur nearer to mapped route proxies than expected under the specified null model. They do not establish intentional route association, geoglyph construction age, or valley-wide spatial organization. The principal contribution is methodological: the study demonstrates how small geoglyph datasets can be evaluated through transparent null-model procedures while making explicit the limits imposed by sample size, surface chronology, spatial uncertainty, and the absence of terrain-based feasibility modeling.